Remote English Teaching Implementation during the Pandemic of Covid-19 - IGA Lokita Purnamika Utami (Journal of Education Technology, 2023)
The appearance of Covid-19 affected many fields, especially the teaching-learning process must be changed from face-to-face teaching-learning process into remote teaching-learning process. This research had been conducted to analyze the remote English teaching implementation during the pandemic of Covid-19, particularly the preparation made, teaching procedure implemented, and student assessment implemented as well as to describe the challenges faced by the English teachers. To conduct the research, a descriptive qualitative method was implemented in this research. The setting of the research were three English teachers in it as the subjects of this research. The researcher used three instruments to obtain the data, such as interview guide, lesson plan evaluation sheet, and observation. The first result shows that the teachers had already prepared their preparation before implementing remote teaching, including lesson plans, learning media/platforms, learning sources, and teaching strategies. The second result related to the teaching procedures during the implementation of remote teaching, it divided into three activities; during pre-activity, the teachers greeted the students and ask them to fill their presence, during whilst-activity they only provided some learning materials, and during post-activity, the teachers end the class by appreciating the students and giving a task. The third result shows that the teachers assessed their students by using various learning assessment media, such as Google Form, Google Drive, and Google Classroom. The last result shows that there were three challenges encountered by the teachers, such as lack of discussion, internet issues from the students, and varying the learning media.